Decolorization pathways of anthraquinone dye Disperse Blue 2BLN by Aspergillus sp. XJ-2 CGMCC12963. Issue 5 (3rd September 2017) - Pan, Huiran; Xu, Xiaolin; Wen, Zhu; Kang, Yanshun; Wang, Xinhao; Ren, Youshan; Huang, Danqi
ABSTRACT: Anthraquinone dye represents an important group of recalcitrant pollutants in dye wastewater. Aspergillus sp XJ-2 CGMCC12963 showed broad-spectrum decolorization ability, which could efficiently decolorize and degrade various anthraquinone dyes (50 mg L −1 ) under microaerophilic condition. And the decolorization rate of 93.3% was achieved at 120 h with Disperse Blue 2BLN (the target dye). Intermediates of degradation were detected by FTIR and GC-MS, which revealed the cleavage of anthraquinone chromophoric group and partial mineralization of target dye. In addition, extracellular manganese peroxidase showed the most closely related to the increasing of decolorization rate and biomass among intracellular and extracellular ligninolytic enzymes. Given these results, 2 possible degraded pathways of target dye by Aspergillus sp XJ-2 CGMCC12963 were proposed first in this work. The degradation of Disperse Blue 2BLN and broad spectrum decolorization ability provided the potential for Aspergillus sp XJ-2 CGMCC12963 in the treatment of wastewater containing anthraquinone dyes.